Penyuluhan DAGUSIBU dan Skrining penyakit Hipertensi dan Diabetes Melitus Pada Siswa MAN 1 KUKAR, Desa Kota Bangun Ulu, Kutai Kartanegara, Kalimantan Timur - Kurniawan, Hery; Maharani, Inggrid Ayu Meytha; Agustina, Adelia (Universitas Pahlawan Tuanku Tambusai, 2024)
Self-medication is a common practice to treat minor health problems, with around 35.2% of families using this method, but it can lead to drug-related problems due to lack of knowledge. Hypertension, which is common among the young and increasing in Indonesia, can be caused by various factors such as obesity and unhealthy diet. Diabetes mellitus, categorised into type 1 and type 2, requires strict management to avoid serious complications. The prevalence of hypertension in Indonesia increased to 34.1% in 2018, while diabetes mellitus reached 21.8%. This program aims to increase public understanding of the correct use, management of drugs and to conduct early detection and preventive efforts for hypertension and diabetes mellitus through the Posbindu program with the Bangun city health centre for MAN 1 KUKAR students. The activities of this programme are in the form of counseling related to DAGUSIBU, counseling and screening of non-communicable diseases hypertension and diabetes mellitus). The results of the evaluation of DAGUSIBU counselling activities obtained good results and the hypertension examination carried out showed the results that there was 1 student in pre-hypertension, as many as 2 students in the stage 1 hypertension category, while 2 students in the stage 2 hypertension category. As well as in the measurement of diabetes mellitus, no students were found to have diabetes mellitus. This event is expected to be an effort to increase knowledge and early detection of non-communicable diseases in students at MAN 1 KUKAR.